PENGARUH EFIKASI DIRI DAN DUKUNGAN SOSIAL ORANG TUA TERHADAP KEMATANGAN KARIR PADA SISWA SMA MUHAMMADIYAH 1 GRESIK - Surya, Afanin Rahmadanti; Rahayuningsih, Idha; Setiawan Wicaksono, Awang (Lafadz Jaya Publisher, 2024)
According to the results of research interviews with students, it was shown that there were 7 people who were immature in their careers and there were 8 students who lacked parental social support. Therefore the aim of the researchers was to determine the influence of Self-Efficacy, Parental Social Support on Career Maturity in SMA Muhammadiyah 1 Gresik Students. This study uses a type of quantitative research. Respondents in this study were Grade 12 students of SMA Muhammadiyah 1 Gresik. The sampling technique used was non-probability sampling by incidental sampling. The sample used was 127 respondents. The results of Test (R2) show a number of 0.062, which means that the Self-Efficacy and Social Support of Parents variables contribute 62% to the career maturity variable, while the remaining 38% is influenced by other variables not examined in this study. According to the hypothesis in line to get a significance result of 0.007 less than 0.05. For Self-Efficacy on Career Maturity, a significance value of 0.168 <0.05 is obtained, which means that there is no significant effect. Meanwhile, between parents' social support for career maturity, a significance value of 0.002 <0.05 is obtained, which means that it is interpreted that there is a significant influence.